UWB double‐ridge waveguide coupler with low loss. Issue 8 (August 2017) - Manoochehri, Omid; Darvazehban, Amin; Erricolo, Danilo
Abstract: A new ultra‐wide band coupler obtained with two crossed double‐ridge waveguides coupled through one aperture is proposed. The main features of the coupler include operating frequency from 6 to 18 GHz, coupling coefficient below −50 dB, return loss of all the ports under −15 dB, minimum directivity 15 dB, small size, and low losses, which make it appropriate for high‐power applications. The whole structure is simulated with CST and HFSS software, fabricated, and measured. Excellent agreement between measured and simulated results was achieved.